Pemberdayaan masyarakat dalam pencegahan penyakit tidak menular dan kekurangan energi kronis pada ibu melalui Posbindu - Setiyawati, Nanik; Meilani, Niken; Santi, Mina Yumei; Sulistyani, Ika Agustina (Universitas Mataram, 2025)
Non-communicable diseases (NCDs) can hinder the achievement of Sustainable Development Goals (SDGs). Posbindu involves the community's participation in conducting early detection activities and monitoring of NCD risk factors, carried out in an integrated, routine, and periodic manner. Integrated NCD risk factors (heart and vascular disease, diabetes, acute obstructive pulmonary disease, and cancer) as well as disorders due to accidents and acts of domestic violence are managed by the community through integrated guidance. These activities combine Posbindu activities to prevent NCDs, anemia, and Chronic Energy Deficiency (CHD) in women in accordance with the direction of Indonesia's Health Transformation. CHD is a condition in which a person's nutritional status is poor and they experience chronic malnutrition that causes health problems. Pregnant women with CHD are at risk of stunting babies. The aim is to empower the community through Posbindu and prevent NCDs, anemia, and CHD. Capillary blood tests using strips revealed that 16.7% of the participants suffered from anemia, 20% had high blood sugar, 23.3% had high cholesterol, and 36.6% had high uric acid levels. At the same time, upper arm circumference measurements revealed that 6.7% had CHD, and blood pressure measurements showed that 40% had hypertension, as a recommendation to integrate anemia and CHD screening into Posbindu activities.